Insights into evolutionary trends in molecular biology tools in microbial screening for biohydrogen production through dark fermentation. (25th October 2018) - Kumar, Gopalakrishnan; Cho, Si-Kyung; Sivagurunathan, Periyasamy; Anburajan, Parthiban; Mahapatra, Durga Madhab; Park, Jeong-Hoon; Pugazhendhi, Arivalagan
Abstract: Access to clean energy is vital to combat global warming and climate change, and nothing but hydrogen could better deliver it with ease to secure future energy needs. Biohydrogen could be produced in different routes including photolysis, water-gas shift reaction, dark, photo-fermentation and combination of both. Dark fermentative hydrogen production (DFHP) is efficient in comparison with photo-fermentation and utilizing organic waste ensures land usage and water for agriculture. Several microbes are involved in the process of biohydrogen production via dark fermentation and characterizing them at molecular level unveils holistic approach and understanding. Limited resources were available in terms of molecular tools for microbial characterization and this paper attempts to review the evolution of advanced molecular techniques including their merits and demerits. Understanding the composition of micro-flora is important in DFHP and could be classified as pure, co-cultures, enriched mixed cultures and mixed microbiota. These cultures act as seed sources for batch and continuous fermentations that help in understanding the efficiency of these methods. The schematics and systematic assessment of the various molecular tools (cloning, PCR-DGGE, FISH, NGS, CE-SSCP) for quantification, identification, detection and characterization of the microbial cell activity have been elaborated. Lastly, a comparative tabulation recapitulates the merits and drawbacks of each technique discussed. This provides valued information for choosing the right kind of microbial and molecular assessment tool for future characterization. Such analysis aids in suitable identification and characterization of microflora as potential biocatalysts for biohydrogen production through dark fermentation. Highlights: Microbiome of DFHP has been overviewed and tabulated. Merits and demerits of molecular technologies for the identification of hydrogen producers highlighted. DFHP pathways and products distribution has been discussed.